Collision with opponents - but not foul play - dominates injury mechanism in professional men`s basketball - Achenbach, L.; Klein, C.; Luig, P.; Bloch, H.; Schneider, D.; Fehske, K. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background To identify injury patterns and mechanisms in professional men`s basketball by means of video match analysis.